The importance of grain size and shape in controlling the dispersion of the Vedde cryptotephra - Jennifer Saxby; Alison Rust; Katharine Cashman; Frances Beckett (Journal of Quaternary Science, 2020)
Volcanic ash is dispersed in the atmosphere according to meteorology and particle properties, including size and shape. However, the multiple definitions of size and shape for non‐spherical particles affect our ability to use physical particle properties to understand tephra transport. Moreover, although particles are often excluded from operational ash dispersion model setups, ash in tephra deposits 1000 km from source can exceed . Here we measure the shape and size of samples of Vedde ash from Iceland, an exceptionally widespread tephra layer in Europe, collected in Iceland and Norway. Using X‐ray computed tomography and optical microscopy, we show that distal ash is more anisotropic than proximate ash, suggesting that shape exerts an important control on tephra dispersion. Shape also impacts particle size measurements. Particle long axis, a parameter often reported by tephrochronologists, is on average greater than geometric size, used by dispersion modellers. By using geometric size and quantifying shape, we can explain the transport of Vedde ash particles more than 1200 km from source. We define a set of best practices for measuring the size and shape of cryptotephra shards and discuss the benefits and limitations of using physical particle properties to understand cryptotephra transport.